DIFFERENT APPROACHES TO THE DEFINITION OF CONTENT AND STRUCTURES OF RESPONSIBILITY (Pedagogy of Higher and Secondary Education, 2022)
The author of the article highlights the different approaches disdinguishing the structural components of responsibility.